MAKING IMAGES-PROJECTIONS IN DRAWING GEOMETRY - Gaziev Nabikhan Umarkhanovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
In connection with the introduction of information and computer technologies into the field of education, as well as in all other fields, it is necessary that the specialists trained in higher education institutions have communicative qualities. For this, great attention is paid to the organization of related subjects on the basis of integrative teaching. In particular, subjects such as "Drawing geometry and computer graphics" or "Engineering and computer graphics" were included in the educational programs of the educational process by the state standard.